“Angajawi”, or, On Being Muslim Nusantara: The Global Argument for Islam (ic) Nusantara - Baso, Ahmad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
The article is an examination of practices, such as the transmission and movement of ideas and knowledge, by which Indonesian Islam or what is called Islam(ic) Nusantara comes into being as a distinct civilizational body, and then considers the ways in which these practices claim a place in a wider Muslim societies. “Angajawi” (being Muslim Nusantara) is a strategic term to convey these practices, while, at the same time, to look closely at the way they constitute the vitality and resilience of Islam(ic) Nusantara cultural riches among the citizens of Muslim world. The method followed in this article is firstly to track down the flow of ideas from Jawi or Nusantara as they were brought about by Indonesian agents of trade, knowledge and pilgrimage to the Holy Land since earlier centuries of the coming of Islam to Indonesia; and then, secondly, to draw our attention to the worldwide Muslim reception of these ideas as the creative energy and qualities of Indonesian Islam in dealing with the problems of humanity. Furthermore, the meaning of “Islam Nusantara”needs to be clarified so as to provide a clear comprehension of the globalized qualities or core ideals of “angajawi”.